Evaluation of the use of moss transplants (Pseudoscleropodium purum) for biomonitoring different forms of air pollutant nitrogen compounds. (June 2016) - Varela, Z.; García-Seoane, R.; Arróniz-Crespo, M.; Carballeira, A.; Fernández, J.A.; Aboal, J.R.
Abstract: We investigated whether three different types of moss transplants (devitalized moss bags with and without cover and auto-irrigated moss transplants) are suitable for use as biomonitors of the deposition of oxidised and/or reduced forms of N. For this purpose, we determined whether the concentration of atmospheric NO2 was related to the % N, δ 15 N and the activity of the enzyme biomarkers phosphomonoesterase (PME) and nitrate reductase (NR) in the tissues of moss transplants. We exposed the transplants in 5 different environments of Galicia (NW Spain) and Cataluña (NE Spain): industrial environments, urban and periurban environments, the surroundings of a cattle farm and in a monitoring site included in the sampling network of the European Monitoring Programme. The results showed that the moss in the auto-irrigated transplants was able of incorporating the N in its tissues because it was metabolically active, whereas in devitalized moss bags transplants, moss simply intercepts physically the N compounds that reached it in particulate or gaseous form. In addition, this devitalization could limit the capacity of moss to capture gaseous compounds ( i.e. reduced N) and to reduce the oxidised compounds that reach the specimens. These findings indicate that devitalized moss transplants cannot be used to monitor either oxidised or reduced N compounds, whereas transplants of metabolically active moss can be used for this purpose. Finally, the NR and PME biomarkers should be used with caution because of the high variability in their activities and the limits of quantification should be evaluated in each case. Highlights: Different moss transplants were tested as biomonitors of N pollution. NR and PME enzyme biomarkers have a high variability in their activities. Devitalized moss transplants could limit the uptake of gaseous N compounds. Transplants with metabolically active moss can be used to biomonitor N pollution. Abstract : Transplants of devitalized specimens of the moss Pseudoscleropodium purum cannot be used to monitor either oxidised or reduced forms of N.